“The road is never straight”: emerging teachers negotiating language and identity - Kajee, Leila (South African Journal of Higher Education, 2016)
The article is based on a qualitative case study of 35 Education students at a historically Afrikaans-medium university in South Africa. The participants in the study are all from disadvantaged educational backgrounds and are speakers of English as an additional language. I use postmodern theory in analysing students’ shifts in language practices, as they negotiate and re-negotiate their identities as writers and as emerging teachers through their narrative writing. Notable too is the grapple between linguistic identity: English, Afrikaans and the mother-tongue, as well as their subsequent constraints and silences.